Budgeting for Social Equity: Exploring the (Nearly) Unknown - Bruce D. McDonald III; Sean A. McCandless (Journal of Social Equity and Public Administration)
Public administration has become increasingly concerned with social equity, particularly in budgetary processes. Local governments have adopted so-called equity budgeting practices, yet little is understood about how and why they are adopted; what budgeting practices are deemed social equity budgeting versus traditional budgeting; what is required to adopt and implement social equity budgeting successfully; and how success is measured. We analyzed government and nonprofit documents on social equity budgeting, followed by interviews with local government budget directors serving “early adopter cities” of social equity budgeting practices. We developed a framework of social equity budgeting practices to link the findings regarding systemic, societal, political, managerial, and legal practices needed for social equity budgeting among these early adopter cities. Five themes were identified that underlie the successful adoption of a social equity lens: broad grassroots efforts, receptive elective leaders, extended community engagement, buy-in by public administrators, and discourse on how to measure equity.